Handbook of the Sociology of Sexualities
XIII, 472 p. 3 illus.
Keywords: This volume provides researchers and scholars with a broad overview of the contributions of social psychologists and sociologists to the study of sexual relationships and sexual expression across the life course. These contributions include analyses of the dynamics of several types of contemporary sexual relationships – e.g., short-term, long-term non-exclusive, and committed. Chapters analyze the influence of major social institutions – e.g., religion, family and economy - on them. The content and scope of this volume have been carefully chosen to balance coverage of traditional emphases – dating, marriage, commercial sex work, sex education - with new and cutting edge materials – embodiment, Trans*, asexualities. Sections review major theoretical perspectives and the principal research methods. Coverage of sexual orientation is integrated throughout. This volume provides excellent resources for anyone interested in research on sexualities.